Wi-Fi fundamentals : a CCNA wireless and CWNA primer - Henry, Jerome (LiveLessons., 2014)
"Wi-Fi Fundamentals LiveLessons is a video tutorial that provides users with over six hours of personal, visual instruction from wireless expert and instructor Jerome Henry. The tutorial contains a series of short instructional videos that demonstrates the concepts and mechanics behind RF, Wi-Fi networks, and 802.11 frame exchanges."--Resource description page.